Analysis of the state of inter-budgetary relations in Kazakhstan at the present stage (Journal of Economic Research & Business Administration, 2015)
"Budgetary relations are considered both on macro - and at a microeconomic level. The first means stability of budget’s replenishment in all levels and acceleration of economic growth rates, the second – efficiency of using the local resources, qualitative granting of social services, development of private business and improvement of aninvestment climate in regions. "
Keywords: Intergovernmental fiscal relations